Inpainting approaches to fill in detector gaps in phase contrast computed tomography. (7th December 2017) - Brun, F; Delogu, P; Longo, R; Dreossi, D; Rigon, L
Abstract: Photon counting semiconductor detectors in radiation imaging present attractive properties, such as high efficiency, low noise, and energy sensitivity. The very complex electronics limits the sensitive area of current devices to a few square cm. This disadvantage is often compensated by tiling a larger matrix with an adequate number of detector units but this usually results in non-negligible insensitive gaps between two adjacent modules. When considering the case of Computed Tomography (CT), these gaps lead to degraded reconstructed images with severe streak and ring artifacts. This work presents two digital image processing solutions to fill in these gaps when considering the specific case of synchrotron radiation x-ray parallel beam phase contrast CT. While not discussed with experimental data, other CT modalities, such as spectral, cone beam and other geometries might benefit from the presented approaches.